Implementation of Creating Technology in 21st Century Learning in Ibtidaiyah Madrasah Padalarang - Yayan Supian; Bambang Qomaruzzaman Anees; Qiqi Yuliati Zaqiah; Muhamad Taufik (STKIP Yapis Dompu, 2023)
The purpose of this research is to analyze the creation of technology by teachers in learning, the technology models used in learning, and to analyze the obstacles in creating learning technology. The research findings obtained through interviews indicate that educators in the Padalarang district have a view that technology in 21st century learning is inevitable and cannot be rejected. However, the creation of technology in 21st century learning is not yet optimal, as the facilities and infrastructure in each madrasah are not adequate, meaning they are not evenly distributed, especially in private madrasahs located in remote areas. Regarding the applications used by madrasah teachers in the Padalarang district, they include internet media, YouTube, Canva application, Kinemaster, AI, PowerPoint, social media platforms (TikTok, Facebook, Instagram), video, Powtoon, Murotal, CapCut, Google Forms, Slidego, Google Forms, Examora, Zoom meetings, and WhatsApp Groups. The obstacles faced by madrasah teachers in the Padalarang district in using technology in learning include network signal/Internet quota, reluctance to learn, resistance to change, monotonous teaching methods, difficulty in finding interesting content, incomplete mastery of technology, and not all areas have good network signals whereas technology requires a place with signal. The methodology used in this research is a qualitative approach, and the data collection technique involved conducting interviews with madrasah teachers in the Padalarang district.